An Empirical Analysis of Nominal and Interacting Groups - Green, Thad B. (Academy of Management Journal, 1975)
No significant differences were found between nominal and interacting groups in number of items generated, number of unique responses, or quality of responses, thus contradicting previously published studies. The findings suggest two conditions under which the purported advantages emanating from nominal grouping are nullified relative to interacting groups.